Urgensi Manajemen Strategik dalam Mengembangkan Lembaga Pendidikan Islam - Suryo Setio Purnomo; Nasrudin Harahap; Nurul Hidayati Murtafiah (Departement of Mathematics Education, 2023)
This study plans to look at all the more profoundly the earnestness of key administration in creating Islamic instructive foundations. The methodology utilized in this paper is expressive subjective where the initial step is to track down data and depict it, then, at that point, gather information deliberately, then make sense of it unmistakably. The consequences of the review show that the idea of system in the administration of Islamic schooling is instructive preparation during the time spent cautiously assessing and organizing what to be finished in Islamic training for the future inside the structure of the interest for objectives. Significantly arranging Islamic instruction contains three things, in particular; (1) instructive objectives, (2) estimation or advancement of arrangements, and (3) execution of instructive plans. In improving the standards of Islamic instructive establishments SWOT examination.